Analysis of Learning Styles for Students with Achievements in Sports - Yasni, Putri Sinta; Hadiwijaya, Rizki; Pratama, Febri Fajar (CV. Rayyan Dwi Bharata, 2023)
This study aims to describe the learning styles used by high achieving students in sports and to describe the characteristic tendencies of the learning styles of high achieving students in sports. The subjects of this study were students who had high achievements in karate. The research was conducted in class V SDN Ciparay, Mangkubumi District, Tasikmalaya City. This study used qualitative research methods. The research data was obtained through data collection techniques, namely observation, interviews and documentation. The research subjects were the home teacher of class V, and one student of class V. Based on the results of the research and discussion of an outstanding student in sports named M, it can be concluded that his learning style shows a tendency for kinesthetic learning styles. Learning through kinesthetic with the characteristics of happy learning to do light physical activities such as walking around when memorizing reading texts, pointing fingers at readings while reading, not being able to sit still for a long time, using body signals when talking or explaining something, writing hands are not neat, explaining something while practicing.